EDUKASI CERDIK SEBAGAI STRATEGI PENCEGAHAN PENYAKIT TIDAK MENULAR (PTM) PADA LANSIA DI KOTA MATARAM - Dewi Nur Sukma Purqoti; Supriyadi, Supriyadi; Zaenal Arifin; Dian Istiana; Baiq Rully Fatmawati; Baik Heni Rispawati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Non-Communicable Diseases (NCDs) such as hypertension, diabetes, and heart disease are among the leading causes of death in the world, with 71% of deaths in 2016 attributed to non-communicable diseases. This has also become the biggest problem in Indonesia, especially among the elderly, one of the efforts to control NCDs is by enhancing the elderly's knowledge about prevention methods, namely through the CERDIK method. This community service activity aims to improve knowledge and awareness of the elderly about NCD prevention through CERDIK behavior education (Check health, Avoid cigarette smoke, Regular physical activity, Healthy diet, Sufficient rest, and Manage stress). The methods used include counseling and conducting health checks. Evaluation results indicate an increase in knowledge after receiving the counseling material. Conclusion: from the results of the service, it can be concluded that the education provided can increase the community's knowledge about the CERDIK method as an effort to prevent non-communicable diseases. It is hoped that the community will be able to implement the CERDIK behavior.